2016
DOI: 10.1007/s11665-016-1958-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ni-B Alloys for Joining of TiB2 Ultra-High-Temperature Ceramic

Abstract: Melting and wetting behavior of Ni 83 B 17 and Ni 50 B 50 alloys on TiB 2 ceramic are investigated upon heating to 1105 and 1050°C, respectively, using the sessile drop technique. Both alloys show a very good wetting on the TiB 2 substrates immediately after incipient melting. Liquid Ni 50 B 50 alloy is revealed not to dissolve TiB 2 , but penetrates along the grain boundaries into the ceramic. Upon heating and melting of the Ni 83 B 17 alloy on TiB 2 , a small amount of ceramic is dissolved and the ternary Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…SEM analysis of the cross‐sectioned solidified sample (Figure A) revealed that the apparent decrease in the contact angle is due to a dissolution of the substrate in the drop . A large crater (depth up to about 230 μm) at the Ni/TiB 2 interface is similar to those formed by Ni/HfB 2 and Ni 83 B 17 /TiB 2 liquid/ceramic interactions. The behavior of liquid Ni on TiB 2 at 1500°C correlates with the wetting test carried out at 1450°C by Samsonov et al .…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…SEM analysis of the cross‐sectioned solidified sample (Figure A) revealed that the apparent decrease in the contact angle is due to a dissolution of the substrate in the drop . A large crater (depth up to about 230 μm) at the Ni/TiB 2 interface is similar to those formed by Ni/HfB 2 and Ni 83 B 17 /TiB 2 liquid/ceramic interactions. The behavior of liquid Ni on TiB 2 at 1500°C correlates with the wetting test carried out at 1450°C by Samsonov et al .…”
Section: Resultsmentioning
confidence: 69%
“…Investigations of high‐temperature wettability and interfacial interactions between liquid metals and ceramics are driven, for example, by the technological demand in obtaining advanced in situ composites, additive manufacturing, and reliable joining of ultrahigh‐temperature ceramics for aggressively chemical and/or thermal environments . In this view, the Ni–Al/TiB 2 system is particularly interesting .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These means that the formation of the TiB 2 phase was more stable than the nickel borides and therefore, the largest amount of boron in the mixture reacted with titanium, resulting in a minimum relation of B/Ni in equilibrium; but enough to the formation of Ni 2 B phase [12,13]. …”
Section: Mechanical Alloyingmentioning
confidence: 99%
“…The high melting temperature, thermal conductivity, elastic-plastic behavior, resistance to erosion, and corrosion make metal-ceramic materials suitable for high-performance applications [2].…”
Section: Introduction 1the Importance Of Metal-ceramic Materialsmentioning
confidence: 99%